Penambahan Puree Daun Semanggi (Marsilia crenata) dalam Pembuatan Kulit Siomay dengan Isian Ayam dan Kupang - Kharis Novia Ramadhan; Ita Fatkhur Romadhoni; Lilis Sulandari; Nugrahani Astuti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Siomay is one of the types of dim sum that is widely found in the Indonesian food industry, with siomay skin as one of the main components to be an attraction on the outside of siomay. In general, siomay skin consists of wheat flour, water, salt, and tapioca. In this study, there is an innovation in siomay skin, namely by adding clover puree in the manufacture of siomay skin. The purpose of this study is to determine the organoleptic quality of siomay skin with the addition of clover leaf puree, nutritional content in siomay skin, and selling price per siomay seed. This type of research is an experiment with the addition of clover leaf puree of 20 g, 30 g, and 40 g, respectively. The collection of organoleptic test data was carried out by observation methods by 30 trained and semi-trained panelists. Organoleptic test data analysis using a single anova test. The results of the addition of clover leaf puree in the manufacture of siomay skin have a real effect on the color and texture of siomay skin, the best results on siomay skin with the addition of clover leaf puree in the amount of 30 grams, the nutritional content of siomay skin with the addition of clover leaf puree is protein 11.05%, antioxidants 98.65 mg, water 33.80%, crude fiber 4.08% and the selling price of one siomay seed is known to be Rp. 3,500.